Peningkatan Hasil Belajar Siswa pada Pembelajaran IPS dengan Menggunakan Pendekatan Kooperatif Group Investigation (GI) dI Kelas V SD - Putri, Dina Wahyu; S, Farida; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research is increase the result of students learning by using investigation group teaching (gi) for grade 5th at elementery school or SDN 23 Marapalam. The subject of this research is students grade 5th and a teacher, for this occasion, the researcher as a teacher and the total number of this research students. The result of this research point out uprading such as:  (a) RPP in 1st cycle, te result score average is 71,42% (B) and 2nd cycle become 89,23% (SB). (b) Assesment of students aspect in 1st cycle is 74,99% (B), as the result score average and 2nd cycle become 93,18% (SB). (c) The result of students score in 1st cycle is 73,85%(B), as a score average and 2nd cycle become 90,90% (SB).(d) Student learning outcomes in cycle I with an average of 67,53% (C) in the second cycle increased to 83,71% (B). It indicates that the result of students score in category social studies learning is improved by using investigation group model.Keywords: group investigation; social studies learning